Two new species of Salvia (Lamiaceae) from the dry forests of Dominican Republic - Itzi Fragoso-Martínez; Gerardo A. Salazar; Emmanuel Martínez-Ambriz; Martin Reith (PhytoKeys)
We describe two new species of Salvia from the Antillean dry forests, belonging to Salvia section Urbania. These species’ names honor two Latin American botanists who have advanced our understanding either of the Dominican flora or the mint family (Lamiaceae). Salvia claseana is found in the Sierra Martín García. It resembles S. calaminthifolia but differs in having strigose stems, rhombic to trullate leaves with a cuneate, decurrent base, and larger flowers. Salvia martineziana inhabits the Sierra de Bahoruco. It resembles Salvia brachyphylla but differs in having strigose stems with retrorse trichomes and flowers disposed in the axils of the distal leaves. We provide descriptions, photographs, a distribution map and an identification key for the species of Salvia section Urbania from the Dominican Republic. Additionally, we sequenced three molecular markers (nrITS, trnL-trnF, and trnH-psbA) for the new taxa and other Dominican and Haitian Salvia species to investigate their phylogenetic relationships.